2018
DOI: 10.12659/msm.908589
|View full text |Cite
|
Sign up to set email alerts
|

Potential Drug–Drug Interactions with Antimicrobials in Hospitalized Patients: A Multicenter Point-Prevalence Study

Abstract: BackgroundImproper use of antimicrobials can cause adverse drug events and high costs. The purpose of this study was to investigate the frequency and potential drug–drug interactions associated with antimicrobials among hospitalized patients.Material/MethodsThis study was conducted on the same day in 5 different hospitals in Turkey. We included patients aged ≥18 years who received at least 1 antimicrobial drug and at least 1 of any other drug. The Micromedex® online drug reference system was used to control an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 29 publications
2
21
1
5
Order By: Relevance
“…The prevalence of pDDI in antimicrobial prescriptions in this study was lower than that described by Piedade et al 21 , in a large hospital in Jequié -BA, which found 46.5% of prescriptions for antimicrobials with some pDDI, also computing the non-significant ones, and that Kuscu et al 15 , which identified 22.7%. On the other hand, although the proportion of clinically relevant pDDI is lower than that found by other authors, their severity was greater than that described by them.…”
Section: Resultscontrasting
confidence: 81%
See 2 more Smart Citations
“…The prevalence of pDDI in antimicrobial prescriptions in this study was lower than that described by Piedade et al 21 , in a large hospital in Jequié -BA, which found 46.5% of prescriptions for antimicrobials with some pDDI, also computing the non-significant ones, and that Kuscu et al 15 , which identified 22.7%. On the other hand, although the proportion of clinically relevant pDDI is lower than that found by other authors, their severity was greater than that described by them.…”
Section: Resultscontrasting
confidence: 81%
“…In recent years, the use of antimicrobials in hospitals has increased dramatically and more than a third of antibiotics are prescribed in disagreement with the guidelines, being a common cause of DRPs and compromising the quality and success of pharmacotherapy and patient safety. 15 The prevalence of prescriptions containing antimicrobials was 36.4% (88), varying from 20% to 50% depending on the inpatient unit and being higher in the ICUs. Rodrigues and Bertoldi 18 identified that 52.4% of ICU patients used at least one antimicrobial in a private hospital in Santa Maria -RS, while Alvim et al 19 observed a prevalence of 25% among patients admitted to the ICU of a hospital in Juiz de Fora -MG, in contrast to the findings by Vicent et al 20 , where 70% of patients received at least one antibiotic during hospitalization of ICU.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We compared the result from Micromedex between the drug list used for metabolic syndrome in human and animal diseases in identity contraindicated and major potential DDIs. The drug list for animal disease treatment identi ed more pairs of contraindicated and major potential DDIs; the reason might be that the drugs used in animals included many drugs related to antiarrhythmic agents, antimicrobials and antihypertensive drugs, which often show a high incidence of potential DDI when prescribed with other drugs [16][17][18]. Veterinary pharmacists should realise when prescribing these drug groups to avoid the severe adverse reactions.…”
Section: Discussionmentioning
confidence: 99%
“…As with any screening tool, effectiveness of DDI checkers is much higher if used in subpopulations with high risk of the target problem. Risk factors for DDIs in patients at ICU were studied in several settings, and the following were repeatedly reported: the length of stay and number of drugs or therapeutic groups prescribed (3)(4)(5)(6). However, a few other risk factors may be of importance, especially prescription of certain drug groups which are prone to DDIs, like anticonvulsants or anticoagulans (3), but their true significance remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%